An improved robust finite-time dissipative control for uncertain fuzzy descriptor systems with disturbance. Issue 8 (11th June 2017) - Su, Zhan; Ai, Jun; Zhang, Qingling; Xiong, Naixue
ABSTRACT: In this paper, finite-time robust control problems are investigated for Takagi– Sugeno fuzzy descriptor systems. We provide a novel sufficient condition for robust finite-time admissibility of Takagi– Sugeno fuzzy descriptor systems, involving a group of coupled linear matrix inequalities (LMIs), which guarantee dissipative performance, reduce conservativeness and improve LMIs forms. Second, corresponding controllers are developed based on both parallel distributed compensation and non-parallel distributed compensation. Simulations demonstrate the effectiveness of the proposed control approach.